2017
DOI: 10.3892/ijo.2017.3905
|View full text |Cite
|
Sign up to set email alerts
|

A liquid biopsy-based method for the detection and quantification of circulating tumor cells in surgical osteosarcoma patients

Abstract: A method for the enumeration and quantification of osteosarcoma (OS) circulating tumor cells (CTCs) is currently not available. A correlation between the number of CTCs and progression-free survival (PFS) has been established for other cancers, but not for OS CTCs. A method was therefore developed for CTC quantification in OS and validated in a prospective cohort of surgical patients with primary and recurrent/metastatic OS (N=23). Human OS cells, acting as CTCs, were enumerated from spiked human peripheral bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 47 publications
(43 reference statements)
1
22
1
1
Order By: Relevance
“…Limited studies of OSA CTC in humans also report a higher number than typically noted for carcinomas, but not nearly as high as those in our study (30,31,44). OSA is a highly aggressive neoplasm in dogs, and circulating OSA cells may at times be observed even on routine blood smear review (data not shown); therefore, frequent CTCs may be a biological feature of the tumor.…”
Section: Discussioncontrasting
confidence: 46%
See 3 more Smart Citations
“…Limited studies of OSA CTC in humans also report a higher number than typically noted for carcinomas, but not nearly as high as those in our study (30,31,44). OSA is a highly aggressive neoplasm in dogs, and circulating OSA cells may at times be observed even on routine blood smear review (data not shown); therefore, frequent CTCs may be a biological feature of the tumor.…”
Section: Discussioncontrasting
confidence: 46%
“…OSA is a highly aggressive neoplasm in dogs, and circulating OSA cells may at times be observed even on routine blood smear review (data not shown); therefore, frequent CTCs may be a biological feature of the tumor. Limited studies of OSA CTC in humans also report a higher number than typically noted for carcinomas, but not nearly as high as those in our study (30,31,44). Strengths of our study are that blood samples from dogs were analyzed multiple times, including immediately before death, which provided a dynamic picture of CTC frequency.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…Therefore, we used an epithelial marker-independent enrichment method combined with immunostaining-fluorescence in situ hybridization (i-FISH) to detect CTCs from NB patients. This EpCAM-independent method has been described by Zhang et al [ 6 ] in a study that quantified CTCs from patients with osteosarcoma, a mesenchymal tumor type that does not express epithelial markers. This method has also been used in the detection of CTCs in gastric [ 7 ], pancreatic [ 8 ] and lung cancer [ 9 ].…”
Section: Introductionmentioning
confidence: 99%